RELIGIOUS AND SPIRITUAL THERAPY IN REHABILITATIONOF PEOPLE WITH MENTAL ILLNESSIN ISLAMIC BOARDING SCHOOL: Terapi Agama Dan Spiritual Dalam Rehabilitasi Orang Penyakit Mental di Sekolah Papan Islam - Sri Padma Sari; Widodo Sarjana (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
ABSTRACT Rehabilitation for people with mental disorders (PMD) plays an important role in helping the healing process. Given the limited number of mental institutions, Islamic boarding schools participate in assisting in the handling of PMD. This study aims to: (i) Identify the religious activities conducted by Islamic boarding schools in the rehabilitation of PMD, (ii) Identify the benefits of spiritual therapy and religious activities in assisting the recovery of PMD. This is a mixed-method research conducted in three boarding schools that provide rehabilitation of the PMD in Yogyakarta, namely Nurul Haromain, Al Islamy and Tetirah Dzikir in February-March 2017. Data from 84 randomly selected respondents with mental disorders were collected using Daily Spiritual Experience Scale (DSES) and PSP (Personal and Social Performance) questionnaires to see the relationship between the spiritual level with changes in personal and social functions in PMD and analyzed using spearman rank correlation test. Qualitative data is conducted by Focus Group Discussion. Results show that there was a relationship between the spiritual level and changes in the personal and social functions of the PMD (p = 0.008; r = 0.286). In addition, most of the religious activities obtained by PMD were praying, reciting the Quran and dhikr. The perceived benefits of religious activities for the PMD were feeling healed from mental illness and the heart becomes more calm. Spiritual therapy in the form of religious activities has an important role for PMD in assisting healing and providing hopes. Activities and living in Islamic boarding schools may enhance PMD’s confidence and social function.